Adolescent Experience And Understanding Of Sexual And Reproductive Health: A Qualitative Study On Street Children And Adolescents - Ilah Muhafilah; Neli Husniawati; Titi Indriyati (Green Publisher Indonesia, 2025)
Introduction: Street children are a highly vulnerable group with limited education, lack of family support, and restricted access to accurate information on sexual and reproductive health (SRH). These conditions place them at higher risk of unintended pregnancy, unsafe abortion, and sexually transmitted infections (STIs), including HIV/AIDS. Objective: This study aims to explore the experiences and understanding of street children regarding sexual and reproductive health. Method: A qualitative design with a phenomenological approach was employed. Ten street children in Jakarta were selected as participants using snowball sampling. Data were collected through in-depth interviews using a semi-structured interview guide and audio recordings. Thematic analysis was conducted through transcription, coding, grouping of subthemes and themes, and using strategy member check, peer debriefing, audit trial and thick description to ensure credibility Result: Analysis generated 32 initial codes, which were grouped into 14 subthemes and condensed into seven major themes: (1) street life and lack of family support; (2) fragmented and myth-based knowledge of puberty and SRH; (3) early sexual experiences and child marriage; (4) sexual harassment and violence on the street; (5) limited knowledge and negative perceptions of contraception; (6) misconceptions about HIV/AIDS and STIs; and (7) unequal sexual and gender norms. These interrelated factors increased vulnerability to risky sexual behaviors, early pregnancy, and exposure to violence. Conclusion: Street children have limited and often inaccurate knowledge of SRH and are highly exposed to risky sexual behaviors without adequate protection.